Philosophical Analysis of the Concept of Historical Consciousness and Axiological Worldview - Dilnoza Innatovna Asadova (Pubmedia Social Sciences and Humanities, 2026)
This article examines the socio-philosophical essence of historical consciousness and the axiological worldview as central categories of contemporary social philosophy. It analyzes historical consciousness as a form of social self-awareness that enables society to interpret the past, construct collective identity, and shape present and future orientations. At the same time, the axiological worldview is explored as a value-based system that evaluates and directs historical interpretation through normative and teleological principles. The study emphasizes the dialectical interrelation between these two concepts, demonstrating that historical consciousness provides the cognitive foundation for social memory, while the axiological worldview determines the hierarchy of values through which historical experience is assessed. Special attention is given to the case of Uzbekistan, where the restoration of historical memory and the reconstruction of national values after independence have become key elements of socio-cultural transformation. The paper argues that only through critical and systematic analysis of historical consciousness and axiological structures can societies ensure spiritual stability, cultural continuity, and sustainable social development in the context of globalization and ideological pluralism.